Anthropological Perspectives on Environmental Communication - Sjölander-Lindqvist, Annelie; Murin, Ivan; Dove, Michael E. (Palgrave Studies in Anthropology of Sustainability, 2022)
In the continuous search for sustainability, the exchange of diverse perspectives, assumptions, and values is indispensable to environmental protection. Through anthropological and ethnographic analyses, this collection addresses how interests, values, and ideologies affect dialogue and sustainability work. Drawing on studies from three continents - Europe, North America, and South America - the paradoxes and the plurality of meanings associated with the creation of sustainable futures are explored. The book focuses on how communication practices collide with organizational frameworks, customary practices, livelihoods, and landscape. In so doing, the authors explore the meanings of environmental communication, pushing beyond environmental advocacy rhetoric to emphasize stronger anthropological engagement within communities to achieve more impactful environmental communication practice. Empirically the book's chapters explore a diverse set of issues, ranging from coastal management in the European north to Native American place naming in Alaska. They further share findings from studies of contaminated land remediation in Sweden, conflicts over water resources in Chile, management of heritage and national parks in Northern Arizona, and cultural transmission in Slovakia. This is an open access book.